2018
DOI: 10.5194/nhess-18-2127-2018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding epistemic uncertainty in large-scale coastal flood risk assessment for present and future climates

Abstract: Abstract. An upscaling of flood risk assessment frameworks beyond regional and national scales has taken place during recent years, with a number of large-scale models emerging as tools for hotspot identification, support for international policymaking, and harmonization of climate change adaptation strategies. There is, however, limited insight into the scaling effects and structural limitations of flood risk models and, therefore, the underlying uncertainty. In light of this, we examine key sources of episte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 70 publications
4
58
0
Order By: Relevance
“…While this study delivers a first assessment of built-environment exposure to ESLs and SLR in New Zealand, information on social and economic impacts and criticality of built-assets is not provided. Several national-and continental-scale flood impact assessments represent built-environments as continuous land cover maps of simplified built-asset typologies for applying economic vulnerability functions [36,[48][49][50]. Our asset-level approach enabled exposure metrics to be aggregated at scales consistent with local authority decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study delivers a first assessment of built-environment exposure to ESLs and SLR in New Zealand, information on social and economic impacts and criticality of built-assets is not provided. Several national-and continental-scale flood impact assessments represent built-environments as continuous land cover maps of simplified built-asset typologies for applying economic vulnerability functions [36,[48][49][50]. Our asset-level approach enabled exposure metrics to be aggregated at scales consistent with local authority decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the assessment is applying a bathtub model that assumes all coastal land below a given water level and hydrologically connected to the ocean or behind protection structures such as levees, as potentially exposed directly or indirectly to flooding from extreme coastal water levels (including groundwater). The bathtub approach tends to overestimate coastal flooding extents at local-scales when caused by episodic events and to a larger extent along mildly sloped terrains [36,37]. In New Zealand, these terrains are representative of most major urban areas with >30,000 population.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, the numerical models are applied in default mode, except for the parameters previously described. It was demonstrated that the hazard modeling input (and, therefore, the output flood maps) can act as important factors affecting the overall uncertainty of flooding risk assessments (e.g., Vousdoukas et al, 2018a). On the other hand, other studies (e.g., Apel et al, 2009;De Moel and Aerts, 2011) conclude that it does not represent a dominant factor, when compared with the uncertainty due to the assumptions on the impact assessment component.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we expect uncertainties in the water surface elevation imposed at the downstream boundary of the hydraulic model domain to strongly influence extreme water levels in the downstream reach. Wave contributions, such as wave setup and wave propagation, are also not directly represented by the BN but can strongly influence water levels [88][89][90]. While this study can be improved by using complementary data at these stations, this typically requires dedicated and extensive studies to properly capture complex coastal and hydrological processes [64,91,92] and is left for future studies.…”
Section: Discussionmentioning
confidence: 99%